Breakthrough pain among cancer patients at oncology units in Northern Ethiopia; a multi-center study - Tekie, Yohanes; Nigatu, Yonas Addisu; Mekonnen, Wudie; Berhe, Yophtahe Woldegerima (Frontiers in Oncology, 2024)
Background Breakthrough cancer pain (BTCP) is a transient exacerbation of pain that affects the length of hospitalization and quality of life of patients. The objective of this study was to determine the prevalence and factors associated with BTCP among cancer patients at oncology units in Northern Ethiopia in 2022. Methods A multi-center cross-sectional study was conducted from April to June 2022. After obtaining ethical approval, data were collected prospectively from 424 adult cancer patients admitted to oncology units. Breakthrough cancer pain was assessed by the numeric rating scale. Descriptive and binary logistic regression analyses were performed to determine the factors associated with BTCP. The strength of association was described in adjusted odds ratio (AOR) with 95% confidence intervals and variables with a P-value < 0.05 were considered to have a statistically significant association with BTCP. Result The prevalence of BTCP among cancer patients was 41.5%. The factors that were found to be associated with BTCP were colorectal cancer (AOR: 7.7, 95% CI: 1.8, 32.3), lung cancer (AOR: 6.9, 95% CI: 1.9, 26.0), metastasis (AOR: 9.3, 95% CI: 3.0, 29.1), mild background pain (AOR: 7.5, 95% CI: 2.5, 22.6), moderate background pain (AOR: 7.0, 95% CI: 2.2, 23.1), severe background pain (AOR: 7.1, 95% CI: 2.2, 22.8), no analgesics taken for background pain (AOR: 5.1, 95% CI: 2.8, 9.3) and uncontrolled background pain (AOR: 3.3, 95% CI: 1.8, 6.1). Conclusion The prevalence of BTCP was high. Colorectal cancer, lung cancer, the presence of metastasis, the presence of background pain, not taking analgesics for background pain, and uncontrolled background pain were significantly associated with BTCP.